Densification of Type I Collagen Matrices as a Model for Cardiac Fibrosis. Issue 22 (7th September 2017) - Worke, Logan J.; Barthold, Jeanne E.; Seelbinder, Benjamin; Novak, Tyler; Main, Russell P.; Harbin, Sherry L.; Neu, Corey P.
Abstract: Cardiac fibrosis is a disease state characterized by excessive collagenous matrix accumulation within the myocardium that can lead to ventricular dilation and systolic failure. Current treatment options are severely lacking due in part to the poor understanding of the complexity of molecular pathways involved in cardiac fibrosis. To close this gap, in vitro model systems that recapitulate the defining features of the fibrotic cellular environment are in need. Type I collagen, a major cardiac extracellular matrix protein and the defining component of fibrotic depositions, is an attractive choice for a fibrosis model, but demonstrates poor mechanical strength due to solubility limits. However, plastic compression of collagen matrices is shown to significantly increase its mechanical properties. Here, confined compression of oligomeric, type I collagen matrices is utilized to resemble defining hallmarks seen in fibrotic tissue such as increased collagen content, fibril thickness, and bulk compressive modulus. Cardiomyocytes seeded on compressed matrices show a strong beating abrogation as observed in cardiac fibrosis. Gene expression analysis of selected fibrosis markers indicates fibrotic activation and cardiomyocyte maturation with regard to the existing literature. With these results, a promising first step toward a facile heart‐on‐chip model is presented to study cardiac fibrosis. Abstract : New collagen matrices are fabricated that are densified to mimic excess matrix accumulation observed in cardiac fibrosis. The densification process also allows for the easy seeding of cells, leading to strong beating abrogation of cardiomyocytes, and fibrotic activation. It is anticipated that this densification process presents a promising first step toward a facile heart‐on‐chip model to study cardiac fibrosis.